AB1117 Burden of Disease in Systemic Lupus Erythematosus Patients Treated with Corticosteroids. (10th June 2014) - Strand, V.; Johnson, J.; Vandeloo, C.; Galateanu, C.; Lobosco, S.
Abstract : Objectives: Current treatments for systemic lupus erythematosus (SLE) include corticosteroids (CS), immunosuppressants (IM), antimalarials (AM) and biologics. SLE treatments, in particular CS, are associated with adverse effects which impact tolerability and treatment-burden. This study sought to assess the use of CS in SLE, and the burden associated with this treatment class. Methods: Data were extracted from the Adelphi 2013 Lupus Disease-Specific Programme (a multinational survey of clinical practice). Physicians completed Patient Record Forms (PRFs) and underwent face-to-face interviews; patients self-reported data including the EQ-5D, Work Productivity and Activity Impairment Index for SLE (WPAI-Lupus) and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) in Patient Self-Completion Records (PSCs). Patient eligibility was determined by physicians; disease activity and severity were based on physician and patient assessment. Results: Data were collected from rheumatologists in the USA (n=97), France (n=37) and Germany (n=35), including PRFs (550/200/207, respectively) and PSCs (303/109/149, respectively). 57%/84%/89% of patients in USA/France/Germany were receiving CS treatment. CS were perceived to be equal/superior to AM, IM and biologics in the ability to rapidly treat flare and pain but inferior in terms of safety/tolerability and inhibition of disease progression. More than half of patients had concerns regarding CS treatment, mainly due to side-effects and fear of long-term use. Patients receiving CS had greater resource use (increased IM/biologic use, greater physician consultation and hospitalization) and worse Health-Related Quality of Life (HRQoL) and activity impairment vs non-CS patients (EQ-5D=0.78 vs 0.87; FACIT-F=34.41 vs 39.56; WPAI=23.30 vs 13.22), but were also associated with worse clinical status (more moderate-to-severe SLE, more "deteriorating" disease state, more rash/pain/flaring/depression, greater organ system involvement). Conclusions: Although a major component of SLE standard of care, clear unmet needs are associated with CS use regarding HRQoL and resource use. Long-term safety and tolerability are also major areas of concern for both physicians and patients. Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: V. Strand Consultant for: UCB Pharma, J. Johnson: None declared, C. Vandeloo Employee of: UCB Pharma, C. Galateanu Employee of: UCB Pharma, S. Lobosco: None declared DOI: 10.1136/annrheumdis-2014-eular.2239